The Reconstruction of Ethnodevelopment in Indonesia: A New Paradigm of Village Development in the Ammatoa Kajang Indigeneous Community, Bulukumba Regency, South Sulawesi - S., Sampean; Sjaf, Sofyan (Masyarakat: Jurnal Sosiologi, 2020)
The implementation of Law Number 6 of 2014 concerning Villages (Village Law) creates a paradox of recognition, especially for indigenous communities which was caused by the contradiction between the value pasang and development practices. The results of previous research have focused more on the use of the Village Fund, the formation of customary villages, and the management and use of customary forests. These findings were used to reconstruct ethnodevelopment in the implementation of the principle of recognition of the Village Law in the Ammatoa Kajang indigenous community. Qualitative data were collected through in-depth interviews and focus group discussions with members and traditional leaders of the Ammatoa indigenous community who understand the ins and outs of village development, culture, community. This paper shows a new paradigm of ethnodevelopment to carry out development in indigenous communities through the identification of customary thinking and development that mainstreams traditions, local knowledge, local wisdom, and the needs of indigenous communities.